The evolution of an industrial cluster in China - Fleisher, Belton; Hu, Dinghuan; McGuire, William; Zhang, Xiaobo (International Food Policy Research Institute, 2009)
We use two rounds of surveys, taken in 2000 and 2008 in the Zhili Township children’s garment cluster in Zhejiang Province, to examine in depth the evolution of this industrial cluster. Firm size has grown on average in terms of output and employment, and increasing divergence in firm sizes has been associated with a significant rise in specialization and outsourcing among firms in the cluster. Although the investment amount needed to start a business has more than tripled, this amount remains low enough that formal bank loans remain an insignificant source of finance. Because of low entry barriers, the number of firms in the cluster has risen, driving down profits and bidding up wages, particularly since the year 2000. Facing severe competition, more firms have begun to upgrade their product quality. By the year 2007, nearly half of the sampled firms had established registered trademarks and nearly 20 percent had become International Office of Standardization (ISO) certified.